The Carbon-Sulfur Link in the Remineralization of Organic Carbon in Surface Sediments - Bradbury, Harold J.; Turchyn, Alexandra V.; Bateson, Adam; Antler, Gilad; Fotherby, Angus; Druhan, Jennifer L.; Greaves, Mervyn; Sevilgen, Duygu S.; Hodell, David A. (Frontiers in Earth Science, 2021)
Here we present the pore fluid carbon and sulfur isotopic composition, along with changes in sulfate concentrations, from a series of sediment located along a depth transect on the Iberian Margin. We use these data to explore the coupling of microbial sulfate reduction to organic carbon oxidation in the uppermost (up to nine meters) sediment. We argue that the combined use of the carbon and sulfur isotopic composition in sedimentary pore fluids, viewed through a 13CDIC versus 34SSO4 cross plot, reveals significant insight into the nature of carbon-sulfur coupling in marine sedimentary pore fluids on continental margins. Our data show systemic changes in the carbon and sulfur isotopic composition of dissolved inorganic carbon (DIC) and sulfate where, at all sites, the carbon isotopic composition of the DIC decreases before the sulfur isotopic composition of sulfate increases. We compare our results to global data and show that this behavior persists over a range of sediment types, locations and water depths. We use a reactive-transport model to show how changes in the amount of DIC in seawater, the carbon isotopic composition of organic matter, the amount of organic carbon oxidation by early diagenetic reactions, and the presence and source of methane influence the carbon and sulfur isotopic composition of sedimentary pore fluids and the shape of the 13CDIC versus 34SSO4 cross plot. The 13C of the organic carbon released during sulfate reduction and sulfate-driven anaerobic oxidation of methane is a major control on the 13CDIC minima in the 13CDIC versus 34SSO4 cross plot, with the 13C of the organic carbon being important during both microbial sulfate reduction and combined sulfate reduction, sulfate-driven AOM and methanogenesis.